2013
DOI: 10.1088/2041-8205/777/2/l37
|View full text |Cite
|
Sign up to set email alerts
|

Bipolar Magnetic Structures Driven by Stratified Turbulence With a Coronal Envelope

Abstract: We report the spontaneous formation of bipolar magnetic structures in direct numerical simulations of stratified forced turbulence with an outer coronal envelope. The turbulence is forced with transverse random waves only in the lower (turbulent) part of the domain. Our initial magnetic field is either uniform in the entire domain or confined to the turbulent layer. After about 1-2 turbulent diffusion times, a bipolar magnetic region of vertical field develops with two coherent circular structures that live du… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 42 publications
6
69
0
Order By: Relevance
“…In the present work, we extend the studies of Warnecke et al (2013b) concerning the detailed dependence on density stratification (Sect. 3.1), magnetic Reynolds number (Sect.…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…In the present work, we extend the studies of Warnecke et al (2013b) concerning the detailed dependence on density stratification (Sect. 3.1), magnetic Reynolds number (Sect.…”
Section: Introductionmentioning
confidence: 72%
“…The model is essentially the same as that of Warnecke et al (2013b), but in this work we vary the stratification, the imposed magnetic field, and the magnetic Reynolds number. We use a Cartesian domain (x, y, z), which has the size…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Brandenburg et al 2010Brandenburg et al , 2012Kemel et al 2012b;Käpylä et al 2012a, and references therein). Further numerical studies have confirmed the existence of NEMPI in direct numerical simulations (DNS) of forced turbulence with weak imposed horizontal (Brandenburg et al 2011) and vertical ) magnetic fields, and in a two-layer system with an upper unforced coronal layer and a lower forced layer (Warnecke et al 2013(Warnecke et al , 2016. With NEMPI, even uniform, sub-equipartition magnetic fields can lead to flux concentrations if there is sufficient scale separation between the forcing scale and the size of the domain in highly stratified turbulence.…”
Section: Introductionmentioning
confidence: 86%
“…However, in highly stratified simulations when potential or vertical field conditions were applied, the studies of Stein & Nordlund (2012) and Warnecke et al (2013) found the possibility of bipolar-region formation. Motivated by these results we apply a vertical field condition in most of the current models.…”
Section: Imposed Horizontal Fieldmentioning
confidence: 99%